The method used in this study was multiple linear regression analysis - Eko Supriyanto; Suci Rejeki (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2023)
The problem arises is STIKOM Surabaya had a will to evaluate the service quality in the AASA based on student’s perception which would be an input to improve the service quality in AASA.Based on the above problem, then this study was held in order to know the influence of service quality in AASA to student’s satisfaction. The method used in this study was multiple linear regression analysis which measures the influence of service quality in AASA section to the satisfaction of the students of Institute of Business and Informatics STIKOM Surabaya and which factors of the dimensions of service quality that need to be improved.According to Parasuraman (1995), Service quality dimensions include 5 dimensions. They are Tangible, Reliability, Responsiveness, Assurance, and Empathy. Tangible is the display or appearance of physical facilities such as; facilities, equipment and personnel appearance. Reliable is the ability to provide service promised. Responsiveness is a willingness to help customers and provide fast and precise service. According to Westbrook in Tjiptono (2014), satisfaction is an assessment of the evaluative global on the use of product or certain service which has been purchased. According to Sulistiowati (2011), The relationship between Service Quality and Customer satisfaction is every service quality improvement will improve student’s satisfaction at LP3I Manyar Surabaya.